Compreensão do típico ideal de técnicos de enfermagem acerca da sistematização da assistência de enfermagem - Salvador, Pétala Tuani Candido de Oliveira (2013)
This study aimed to understand the typical ideal of the nursing technician about the systematization of nursing care in the light of the theoretical framework of Alfred Schutz. It is a comprehensive phenomenological research, using the theoretical framework of Alfred Schutz. For the unveiling of the phenomenon (the typical ideal of the nursing technician about the systematization of nursing care), the search process was configured from the proposed guiding principles for a research methodology based on the work itself of Schutz held by Zeferino (2010) in his PhD. For data collection, we used the focus group technique, counting on the collaboration of thirteen practical nurses working in a university hospital in Rio Grande do Norte, who responded positively to the inclusion criteria: working in the study hospital, performing care direct to patients. Forty-four subjects showed interest in participating, being held a draw for selection of the research sample, consisting of 14 professionals, one of whom did not attend the gathering of data collection. The focus group, entitled "What I think about the systematization of nursing care", took place on February 15th, 2013, totaling 101 minutes. It was performed according to the Experiential Education Humanescent using building posters as projective technique, from the key question: "What is the systematization of nursing care for you?". In order to understand some of the biographical situation of the participants, a questionnaire was administered to study participants. From the agreement of the subjects, the focus group was recorded and photographed with the cooperation of one reporter and two other employees. We used Microsoft Word 2010 to perform the transcript of the meeting and Microsoft Excel 2010 for synthesizing the results via a spreadsheet. The study followed the ethical and legal principles that govern scientific research on humans, recommended in Resolution nº 196/96, it was approved by Opinion Embodied Ethics Committee in Research of UFRN (Federal University of Rio Grande do Norte), nº 98 424, of August 31th, 2012, CAAE No. 05906912.0.0000.5537. The analysis of the nursing staff speeches, along with the contemplation of their posters and their written descriptions, allowed from the guiding principles of Zeferino (2010), in light of the reference of Alfred Schutz, unveiling the typical ideal of nursing technicians about the systematization of nursing care, passing four themes: typing of the concept of systematization of nursing care; benefits, which resulted in the reasons to believe in the positivity of this working tool; experienced problems, revealing the world of everyday life of nursing professionals, and possibilities for improvement. It was concluded that the nursing technicians are unaware of the systematization of nursing care. However, they typify a very positive perception about the same, especially with regard to improvements that may foster care